Diagnostic and Preventive Approaches for Dental Caries in Children: A Review - Shahryar Karami; Nazanin Ghobadi; Hasan Karami (Mazandaran University of Medical Sciences, 2017)
Context Oral health status plays an essential role in human health. Recently, enhancement in oral health caries has been noted in both developed and developing countries. Dental caries is still very common among children. Screening and preventive interventions is necessary. The aim of this study was to review the diagnostic and preventive approaches for dental caries in children. Evidence Acquisition Searching PubMed, Medline, the Cochrane Library (for 5 recent years from 2011 - 2016), and reference lists for keywords and phrases such as "dental caries in children" and prevention and diagnosis, we included trials and controlled observational studies regarding the diagnosis and preventive techniques for dental caries in children. Results We found no study demonstrating the effects of screening by primary care providers on clinical outcomes. In a cohort study, pediatrician examination associated with a sensitivity of 0.76 was reported to identify dental caries in children. The results of the new randomized trials that were confirmed by previous studies showed that the efficacy of fluoride varnish is more than no varnish in reduction of dental caries from 18% to 59%. Some of the trials regarding xylitol had no results regarding the effects on dental caries. New observational studies have shown an association between early childhood fluoride use and enamel fluorosis. There is no evidence on the accuracy of prediction instruments in primary care settings. Conclusions We found no direct evidence that reveals that screening by primary care clinicians can decrease early childhood caries. Previous evidences reviewed by the United State Preventive Services Task Force demonstrated that oral fluoride supplementation is effective in decreasing caries incidences, and recent evidences supported the effectiveness of fluoride varnish in higher-risk children.